EVALUATION OF BLOOD GLUCOSE TESTING USING CONTOUR® PLUS GLUCOMETER - Beauty, Venny; Sukartini, Ninik (Indonesian Association of Clinical Pathologist and Medical laboratory, 2018)
The use of glucometers has been widely recommended to help patients in controlling their blood glucose level. This study compared the blood glucose level measured by Contour® Plus glucometer and Cobas c501 chemistry analyzer, as the reference method. The study design was cross-sectional and conducted in the Dr. Cipto Mangunkusumo Hospital in April 2017. Study materials were 120 capillary blood examined by Contour® Plus glucometer and plasma analyzed by Cobas c501 chemistry analyzer. Precision, correlation, accuracy, and clinical accuracy tests were performed based on ISO 15197:2013, using Parkes error grid analysis. Contour® Plus glucometer yielded a CV of 1.56-2.2%, following the recommendation of the American Diabetes Association, of <5%, there was a strong positive correlation between the glucose level of capillary blood and plasma (r=0.997). Accuracy test based on ISO 15197:2013 showed that 100% of capillary blood glucose deviations were within the ±15 mg/dL range for glucose level <100 mg/dL and ±15% range for glucose level ≥100 mg/dL. Clinical accuracy test with Parkes error grid showed 100% of results were in zone A. Contour® Plus glucometer test results met the ISO 15197:2013 criteria, so the results were proportional to the reference method’s results and clinically acceptable. Contour® Plus glucometer is safe to be used in blood glucose monitoring, as long as careful attention is given to the device specifications.